Case report: Cutaneous metastases as a first manifestation from breast cancer with concurrent gastric metastases - Xu, Lulu; Wang, Congcong; Yang, Xiaoling; Dong, Liangliang (Frontiers in Pharmacology, 2024)
Breast cancer represents a leading cause of malignancy among Chinese women, posing a significant health burden. The diagnosis of metastatic breast cancer, particularly to uncommon sites like the skin and stomach, presents distinct challenges.This case report describes a 71-year-old Chinese women with a persistent back rash lasting more than 6 months. Physical examination revealed red papules on her back. Immunohistochemistry confirmed positive for cytokeratin 7(CK7), GATA-3 and GCDFP15, as well as negative staining of cytokeratin 20 (CK20), suggesting breast cancer metastasis. Further evaluation revealed a breast nodule and axillary lymph node enlargement, with biopsies confirming invasive lobular carcinoma (ILC). Abdominal computed tomography (CT) revealed thickening of the gastric and ascending colon walls. Gastroscopy revealed chronic superficial atrophic gastritis. However, gastric metastasis was further confirmed by pathology. The patient initiated endocrine therapy with fulvestrant and exemestane, resulting in rash resolution and stable breast and stomach lesions after three months. Overall, the patient is experiencing an improvement in her condition and remains stable while continuing treatment.This case highlights the importance of considering atypical metastatic patterns in breast cancer and the potential efficacy of endocrine therapies in managing such cases. Moreover, it emphasizes the need for vigilance in breast cancer patients, especially those with ILC, as gastrointestinal symptoms may indicate gastric metastasis (GMs). Ultimately, early detection and appropriate treatment strategies, such as endocrine therapy, can contribute to improved outcomes in these challenging cases.Keywords：cutaneous metastases, breast cancer, gastric metastases, invasive lobular carcinoma, endocrine therapy * The two corresponding authors contribute equally to this work.LLD provided the case. XLY conducted pathological analysis. LLX and CCW drafted the manuscript. LLD were involved in critically revising the manuscript. All authors have read and approved the manuscript.